Bangsa Cina; Antara Profetis Dan Diabolistik - Ilham Darajat (Tsaqofah, 2019)
Comprehensive understanding of prophetic text which is correlated with anthropological phenomena is difficult to achieve. This occurs because there are a number of reading subjectivity and scientific traditions that have been hegemonized by the domination of authoritative communities and their interests. Likewise, what happened to the phenomenon of humiliation (the Chinese nation and its civilization), instead of obtaining a source of prophetic text that placed the nation on an egalitarian anthropological degree with other nations, it received sharp attention because of its strong correlation with the text "Yes, Juj and The demonic ma'juj ”. While it is known that the Chinese nation has contributed a lot to Islamic civilization, until it is enshrined in one text which is sadly debated. This paper presents a view of the entity of the Chinese Nation and its action in the corridor of the revelation text to find out its ambiguous position between the factor of harmony or destruction. The method used in this paper uses an explanatory method, where several hypotheses are tested and then affirmed or negated.